La Translation de S. Jean Chrysostome BHG 877h: une œuvre de l'empereur Léon VI - Devos, Paul (Analecta Bollandiana, 1989)
Leo VI the Wise was known to be the author of the rather long Life of John Chrysostom BHG 880. A comparison of its style with that of the Translation BHG 877h affords the main proof that the same Emperor also wrote this Eulogy, to be preached in the Basilica of the Roly Apostles in Constantinople.